Carbapenem-Resistant Enterobacteriaceae (CRE) among Children with Cancer: Predictors of Mortality and Treatment Outcome - Youssef Madney; Shaimaa Aboubakr; Reham Khedr; Hanafy Hafez; Naglaa Ahmed; Khaled Elsheshtawy; Mervat Elanany; Abdelhamid Salahelden; Lobna Shalaby; Ola Galal Behairy (MDPI AG, 2023)
Carbapenem-resistant Enterobacteriaceae (CRE) is an important emerging threat among pediatric cancer patients, with a high mortality rate. This retrospective study included all pediatric cancer patients with (CRE) bloodstream infections (BSIs) at a children's cancer hospital in Egypt (2013-2017). Two hundred and fifty-four pediatric cancer patients with CRE BSI were identified; 74% had hematological malignancies, and 26% had solid tumors. Acute myeloid leukemia was the most common hematological malignancy (50%). The main clinical features for acquiring CRE-BSI were previous antibiotics exposure (90%), profound neutropenia (84%), prolonged steroid use (45%), previous colonization with a resistant pathogen (35%), ICU admission within 90 days (28%), and central venous catheter use (24%). E. coli was the most common isolated pathogen (56%), followed by Klebsiella pneumoniae (37%). All isolates were resistant to carbapenem with an MIC < 4-8 μg/mL in 100 (45%) and >8 μg/mL in 153 (55%). The overall mortality rate was 57%, and 30 day mortality was reported in 30%. Upon multivariate analysis, for the patients with Klebsiella pneumoniae BSI, carbapenem resistance with an MIC > 8 μg/mL and associated typhlitis or pneumonia were predictors of poor outcome. In conclusion, CRE-BSI is a major threat among pediatric cancer patients in limited resource countries with limited options for treatment. Antimicrobial stewardship for early detection through routine screening, adequate empirical treatment, and timely adequate therapy may impact the outcome for such high-risk patient groups.